Implementing a digital mental health intervention for individuals with psychosis - a multi-country qualitative study - Pemovska, Tamara; Arënliu, Aliriza; Konjufca, Jon; Uka, Fitim; Hunter, Jennifer; Bajraktarov, Stojan; Stevović, Lidija Injac; Jerotić, Stefan; Kulenović, Alma Džubur; Novotni, A; Novotni, Ljubisa; Radojičić, Tamara; et al. (Springer Science and Business Media LLC, 2021)
Implementation of psychosocial interventions in mental health services has the potential to improve the treatment of psychosis spectrum disorders (PSD) in low- and middle-income countries (LMICs) where care is predominantly focused on pharmacotherapy. The first step is to understand the views of key stakeholders. We conducted a multi-language qualitative study to explore the contextual barriers and facilitators to implementation of a cost-effective, digital psychosocial intervention, called DIALOG+, for treating PSD. DIALOG+ builds on existing clinician-patient relationships without requiring development of new services, making it well-fitting for healthcare systems with scarce resources.